2011
DOI: 10.1007/s11005-011-0476-y
|View full text |Cite
|
Sign up to set email alerts
|

Formality Theorem for Hochschild Cochains via Transfer

Abstract: Belatedly to Simon Lyakhovich on the occasion of his 50th birthday. AbstractWe construct a 2-colored operad Ger + ∞ which, on the one hand, extends the operad Ger ∞ governing homotopy Gerstenhaber algebras and, on the other hand, extends the 2-colored operad governing open-closed homotopy algebras (OCHA). We show that Tamarkin's Ger ∞ -structure on the Hochschild cochain complex C • (A, A) of an A ∞algebra A extends naturally to a Ger + ∞ -structure on the pair (C • (A, A), A) . We show that a formality quasi-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…As an application, in Theorem 4.2.2 we show that the spectral sequence E(SC) of the Swiss-cheese operad collapses at the second stage, proving a conjecture by A. Voronov in [17]. The relation (modulo (de)suspension) between E 1 (SC) and the cobar construction of the cohomology cooperad H * (SC) is well known [2], but in our setting it is slightly different, so a proof is given in Lemma 4.1.1. Finally, using that Lemma and the Koszul duality theory in the quadratic-linear framework, we prove that the spectral sequence given by the stratified structure of SC induces on H * (SC) an operad structure that is different from the one induced by the topological operad structure of SC, while the S-module structure is the same.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…As an application, in Theorem 4.2.2 we show that the spectral sequence E(SC) of the Swiss-cheese operad collapses at the second stage, proving a conjecture by A. Voronov in [17]. The relation (modulo (de)suspension) between E 1 (SC) and the cobar construction of the cohomology cooperad H * (SC) is well known [2], but in our setting it is slightly different, so a proof is given in Lemma 4.1.1. Finally, using that Lemma and the Koszul duality theory in the quadratic-linear framework, we prove that the spectral sequence given by the stratified structure of SC induces on H * (SC) an operad structure that is different from the one induced by the topological operad structure of SC, while the S-module structure is the same.…”
supporting
confidence: 51%
“…We also show that the operad structure induced on H * (SC) by the spectral sequence of its stratified version differs from the structure given by the topological operad structure of SC. The difference between the two operad structures in H * (SC) is explored in terms of the Koszul duality theory for inhomogeneous quadratic operads developed by Tonks and Vallette in [5].Among the related algebraic structures are Kajiura and Stasheff's OCHA [11,10], Leibniz pairs [3] and extensions of those considered by Dolgushev [2]. The relation between OCHAS, Leibniz pairs and the Swiss-cheese operad has been carefully studied by the authors in [9], where the zeroth homology of the Swiss-cheese operad SC were related to the first row of the spectral sequence associated to the Kontsevich compactification.…”
mentioning
confidence: 99%
“…The left hand side of the quasi-isomorphism is minimal and algebras over it are OCHA as pointed out by Dolgushev in [3] (see section 7.1). The result, however, is not totally satisfying because H 0 (SC)…”
Section: Introductionmentioning
confidence: 93%
“…But he did not prove that the operad is Koszul. In [3], Dolgushev showed that OCHA correspond to algebras over Ω(D), where D is a cooperad that will be specified later, but without proving that D is Koszul. The aim of our paper is to prove that the operads involved are Koszul, justifying completely that SHLP and OCHA are "strong homotopy" algebras over an operad.…”
Section: Introductionmentioning
confidence: 99%
“…Let us comment some related results. For d = 2, Dolgushev studies in [3] the first sheet of the homology spectral sequence for the Fulton-MacPherson version of the Swiss-cheese operad and proves that it is not formal. However, this does not imply the non-formality of SC 2 , because we proved with E. Hoefel in [7] that the homology spectral sequence, though collapsing at page 2, does not converge as an operad, to the homology operad of SC 2 .…”
Section: Introductionmentioning
confidence: 99%